Evaluation of combined prescription of rocker sole shoes and custom-made foot orthoses for the treatment of plantar fasciitis - Fong, Daniel Tik-Pui; Pang, Kai-Yip; Chung, Mandy Man-Ling; Hung, Aaron See-Long; Chan, Kai-Ming (Clinical biomechanics (Bristol), 2012)
It is a routine practice to prescribe a combination of rocker shoes and custom-made foot orthoses for patients with plantar fasciitis. Recently, there has been a debate on this practice, and studies have shown that the individual prescription of rocker shoes or custom-made foot orthoses is effective in treating plantar fasciitis. The aim of this study was to evaluate and compare the immediate therapeutic effects of individually prescribed rocker sole shoes and custom-made foot orthoses, and a combined prescription of them on plantar fasciitis. This was a cross-over study. Fifteen patients with unilateral plantar fasciitis were recruited; they were from both genders and aged between 40 and 65. Subjects performed walking trials which consisted of one ‘unshod’ condition and four ‘shod’ conditions while wearing baseline shoes, rocker shoes, baseline shoes with foot orthotics, and rocker shoes with foot orthotics. The study outcome measures were the immediate heel pain intensity levels as reflected by visual analog scale pain ratings and the corresponding dynamic plantar pressure redistribution patterns as evaluated by a pressure insole system. The results showed that a combination of rocker shoes and foot orthoses produced a significantly lower visual analog scale pain score (9.7mm) than rocker shoes (30.9mm) and foot orthoses (29.5mm). With regard to baseline shoes, it also significantly reduced the greatest amount of medial heel peak pressure (−33.58%) without overloading other plantar regions when compared to rocker shoes (−7.99%) and foot orthoses (−28.82%). The findings indicate that a combined prescription of rocker sole shoes and custom-made foot orthoses had greater immediate therapeutic effects compared to when each treatment had been individually prescribed.